Evolutionary Perspectives on Hermaphroditism in Fishes - Avise, J.C.; Mank, J.E. (Sexual development, 2009)
Hermaphroditism is a derived and polyphyletic condition in fishes, documented in about 2% of all extant teleost species scattered across more than 20 taxonomic families in 9 orders. It shows a variety of expressions that can be categorized into sequential and synchronous modes. Among the sequential hermaphrodites are protogynous species in which an individual begins reproductive life as a female and later may switch to male, protandrous species in which a fish starts as a male and later may switch to female, and serial bi-directional sex changers. Among the synchronous hermaphrodites (in which an individual can simultaneously produce eggs and sperm) are several outcrossing and one predominantly selfing species. A few species also consist of mixtures of hermaphroditic and single-sex individuals. All of these reproductive categories have been the subject of numerous theoretical and empirical treatments from an evolutionary perspective. Here we highlight some of the major conclusions from these studies, which collectively have been informative on a variety of biological topics related to reproductive modes, gender allocations, sexual conflict and gamesmanship, mating systems, and life-history tradeoffs.